MENGHAFAL AL-QURAN: TINJAUAN FUNGSI KOGNITIF - Adriani, Donna; Amani, Patwa; Putri, Mustika Anggiane; Imran, Yudhisman; Fauzi, Ahmad (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2024)
Cognitive function is a mental process consisting of knowledge, information processing, and reasoning. Cognitive functions include the domains of perception, memory, learning, attention, decision-making, and language skills. Assessment of cognitive functions consists of attention and concentration, executive function, memory, language, visuoconstruction skills, conceptual thinking, calculation, and orientation. Cognitive disorder is a maladaptive response characterized by impaired memory, disorientation, incoherence and difficulty thinking logically. Memorization involves various complex processes called basic cognitive processes which include encoding, storing, and recalling memories, because these processes occur in many memory systems that function differently but are interconnected with one another. Al-Quran is the holy book of Muslims that comes from Allah SWT and was revealed through the Prophet Muhammad SAW. Memorizing the Al-Quran can stimulate the neurotrophin factor. In adulthood, there is a decrease in cognitive function of 6.7%. Cognitive function can be assessed from the serum levels of Brain Derived Neurotrophic Factor (BDNF) and serum Nerve Growth Factor (NGF). Brain Derived Neurotrophic Factor is a protein that increases the survival of neurons and synapses that play a role in learning and memory processes. Nerve Growth Factor is a protein that plays a role in the growth, development and maintenance of nerve cells. The purpose of this study is to explain physiologically the effect of memorizing the Al-Quran on cognitive function in terms of serum BDNF and NGF levels. Based on the results of several studies, it was found that memorizing the Al-Quran continuously can improve cognitive function.